Attitudes of dental students towards paediatric dental behaviour guidance - Maria Shindova; Ani Belcheva (Universidade Estadual de Campinas, 2021)
Aim: To compare the pre-clinical and clinical students` perceptions about the non-pharmacological behaviour management techniques in paediatric dentistry and to investigate the influence of the dental curriculum on the students` knowledge regarding this issue. Methods: A total of 283 students from the IV-and X-semester completed a questionnaire, consisted of 12 statements, describing the nonpharmacological behaviour management techniques for the treatment of paediatric dental patients. The acceptability rate was evaluated with a Likert scale ranging from 1 to 5. Results: The students from all courses demonstrated high acceptance for Reinforcement and Desensitization techniques and low for the Negative reinforcement and Physical restraint. The comparison between the perceptions of the pre-clinical and clinical students demonstrated a statistically significant increase in the acceptance of the physical restraint, along with Nonverbal communication, Modelling and Parental presence/absence (p<0.05). Conclusion: The results provide information about the students' knowledge and skills in behaviour management techniques together with some insights about how the educational process can modify the students` perceptions and views in dealing with paediatric dental patients.